2023
DOI: 10.1002/smll.202304166
|View full text |Cite
|
Sign up to set email alerts
|

Chirality‐Induced Spin Selectivity of Chiral 2D Perovskite Enabling Efficient Spin‐Dependent Oxygen Evolution Reaction

Abstract: The sluggish and complex multi‐step oxygen evolution reaction remains an obstacle to bias‐free photoelectrochemical water‐splitting systems. Several theoretical studies have suggested that spin‐aligned intermediate radicals can significantly enhance the kinetic rates for oxygen generation. Herein, it is reported that the chirality‐induced spin selectivity phenomena can become an impressive approach by adopting chiral 2D organic–inorganic hybrid perovskites as a spin‐filtering layer on the photoanode. This chir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…Conversely, when the spins of the radicals are parallel, the system resides on a triplet potential energy surface, promoting the production of O 2 . , Notably, in chiral molecules the antiparallel pathway is suppressed, leading to increased O 2 production. This is consistent with mechanisms proposed in previous reports where the spin-polarized reaction intermediates on chiral catalysts promote the reaction pathway for triplet O 2 . , The cumulative effect of CISS and H ext on the chiral s-Fe 3 O 4 system was investigated, as shown in Figure d. The combined impact of chirality and magnetic field resulted in a higher enhancement (89% increase in current density at 1.8 V vs RHE) than the corresponding individual effects.…”
supporting
confidence: 89%
“…Conversely, when the spins of the radicals are parallel, the system resides on a triplet potential energy surface, promoting the production of O 2 . , Notably, in chiral molecules the antiparallel pathway is suppressed, leading to increased O 2 production. This is consistent with mechanisms proposed in previous reports where the spin-polarized reaction intermediates on chiral catalysts promote the reaction pathway for triplet O 2 . , The cumulative effect of CISS and H ext on the chiral s-Fe 3 O 4 system was investigated, as shown in Figure d. The combined impact of chirality and magnetic field resulted in a higher enhancement (89% increase in current density at 1.8 V vs RHE) than the corresponding individual effects.…”
supporting
confidence: 89%
“…This was further validated by the achiral CuO, where no significant current preference was observed regardless of the tip magnetization direction (Figure d). Similar effects have been previously observed in chiral organic materials. , Based on the measured I–V difference, spin polarization ( P ) can be quantified by the equation , P = I up I down I up + I down × 100 % where I up and I down denote the currents measured when the tip was magnetized in the upward or downward directions, respectively. The magnitude of spin polarization of chiral copper oxide could reach 80% (Figure S13).…”
Section: Resultssupporting
confidence: 54%
“…To evaluate the spin selectivity of the synthesized chiral CuO nanoparticles, magnetic conductive probe-atomic force microscopy (mc-AFM) was employed. ,, CuO films were prepared by drop-casting l / d / dl -CuO (▲) samples onto fluorine-doped tin oxide (FTO)-coated glass substrates. The experimental setup, illustrated in Figure a, involved a conducting probe with CoCr coating that was first premagnetized with different magnetization directions in either an upward or downward direction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be interesting and significant that different circularly polarized light can modulate the spin state of catalysts, thus leading to the selective catalytic production of different chiral molecules. Recent research has revealed that chiral-induced spin selectivity (CISS) can be observed in various spin-dependent optoelectronics and electrochemistry. CISS suggests that the molecular chirality and electron spin of chiral systems are highly correlated, meaning that electron spins become polarized as they pass through chiral systems. It has been proposed that the spin-polarized electrons generated by the CISS can interact with the catalyst surface, leading to an enhanced activity in the OER/ORR.…”
Section: Discussionmentioning
confidence: 99%